Rotational Motion Modelling for Numerical Analysis of Electric Machines - Marcsa, D. (Acta Technica Jaurinensis, 2017)
The paper presents a brief review of the movement modelling methods of electric machines and the two most common used torque calculation techniques. After the classification of single-layer moving band methods, a low computation cost and an easily realisable new variant of this movement modelling technique is proposed. To study the accuracy of proposed moving band technique equipped with Arkkio's method and Maxwell's stress tensor method for torque calculation an international benchmark problem used. Further, to check the applicability, the proposed method has been used to analyse a three-phase switched reluctance motor. The results of proposed method have been compared to analytical and numerical results.